Risk Factors Affecting Quality of Life in Chronic Limb Threatening Ischemia Patients - Wu R; Yu Y; Guo J; Gao X; Tong Z; Guo J; Cui S; Zhang C; Guo L (Patient Preference and Adherence)
Rui Wu,* Yuan Yu,* Julong Guo,* Xixiang Gao, Zhu Tong, Jianming Guo, Shijun Cui, Chengchao Zhang, Lianrui Guo Department of Vascular Surgery, Xuanwu Hospital, Capital Medical University, Beijing, 100053, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lianrui Guo, Department of Vascular Surgery, Xuanwu Hospital, Capital Medical University, No. 45 Changchun Street, Xicheng District, Beijing, 100053, People’s Republic of China, Tel +86 15510170321, Email lianruiguo@sina.comPurpose: To analyze the independent risk factors affecting quality of life (QoL) in chronic limb threatening ischemia (CLTI) patients, with a particular focus on the role of the Wound, Ischemia, and foot Infection (WIfI) classification. Understanding these relationships could provide insights into optimizing patient management and improving their overall QoL.Patients and Methods: This study was conducted at our center from January 2021 to January 2024. Hospitalized patients diagnosed with CLTI (Rutherford categories 4– 6) were enrolled for QoL assessment using the Vascular Quality of Life Questionnaire (VascuQoL). We analyzed the differences in the scores of vascuQoL and its five dimensions among patients grouped by different WIfI stages. A linear regression model was used to identify independent risk factors of overall VascuQoL scores and its different dimensions.Results: This study included 309 patients with an average age of 70.11 years; 30.1% were female. The mean baseline VascuQoL score was 2.02 ± 0.83. According to the WIfI classification, patients were distributed as follows: 15.53% stage 4, 39.16% stage 3, 27.83% stage 2, and 17.48% stage 1. WIfI classification emerged as a key independent predictor, significantly affecting overall VascuQoL scores (β=− 0.15, 95% CI − 0.24 to − 0.06, P=0.002) and four out of five QoL dimensions (activity, symptoms, emotional well-being, and social interactions). Female sex, smoking history, cerebral infarction history, and previous limb revascularization also affect the quality of life from different dimensions or as a whole.Conclusion: CLTI markedly worsens patients’ QoL, with WIfI stage playing a crucial role in determining outcomes.Keywords: chronic limb threatening ischemia, peripheral arterial disease, quality of life, WIfI classification system